2017
DOI: 10.1111/ijfs.13383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pineapple, apple and melon by‐products on cookies: physicochemical and sensory aspects

Abstract: Summary Physicochemical and sensory effects were investigated regarding the partial substitution of wheat flour in cookies with flours made of pineapple, apple and melon by‐products, in the concentrations 5%, 10% and 15%. Cookies with 15% of melon flour were prominent in relation to the nutritional aspects, especially about the contents of fibres (4.67–6.46%) and ash (1.74–2.25%). The use of these by‐products resulted in slightly darker cookies, with variations in diameter and in the expansion factor. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 14 publications
6
37
1
9
Order By: Relevance
“…In a previous study (Toledo, Nunes, Silva, Spoto, & Canniatti-Brazaca, 2017), it was observed that cookies prepared with pineapple central axis presented satisfactory results from the sensory and technological properties, whereas cookies made with melon by-products showed more unsatisfactory results than the control treatment. It is known that besides these aspects, investigating the presence of bioactive compounds, such as phenolic acids and flavonoids in these cookies may be relevant to determine the effects of the use of by-products on the antioxidant capacity of this foodstuff.…”
mentioning
confidence: 91%
“…In a previous study (Toledo, Nunes, Silva, Spoto, & Canniatti-Brazaca, 2017), it was observed that cookies prepared with pineapple central axis presented satisfactory results from the sensory and technological properties, whereas cookies made with melon by-products showed more unsatisfactory results than the control treatment. It is known that besides these aspects, investigating the presence of bioactive compounds, such as phenolic acids and flavonoids in these cookies may be relevant to determine the effects of the use of by-products on the antioxidant capacity of this foodstuff.…”
mentioning
confidence: 91%
“…In total, four formulations were developed, one being the control (cookie control [CCT]), which was prepared only with wheat flour, whereas in the others the wheat flour was partially replaced by 15% of the following by‐products: apple (cookie containing apple by‐product [CAP]), melon (cookie containing melon by‐product [CML]), and pineapple (cookie containing pineapple by‐product [CPI]). Previous analyses (Toledo et al, ) showed that biscuits containing 15% of by‐products presented better technological, sensory, and nutritional properties, and therefore, these were the formulations addressed in the present study.…”
Section: Methodsmentioning
confidence: 90%
“…Besides the antinutritional factor, these results may be associated with the fiber content of the biscuits. In previous assays (Toledo et al, 2017), it was observed that cookies with fruit by-products presented higher fiber contents than the control. Likewise, depending on the amount and type of fiber, calcium solubility can be affected (Silva, Rebellato, Greiner, & Pallone, 2017).…”
Section: Mineral Bioavailability By Caco-2 Cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…The addition of pineapple byproducts significantly enhanced the nutritional properties as well as the taste of food products. Cookies enriched with wheat flour partially substituted by pineapple flour byproducts gave high fiber levels, a consumers’ acceptance of 97%, and a buying intention of 53% (Toledo, Nunes, Silva, Spoto, & Canniatti‐Brazaca, ). Similar results were observed in cereal bars supplemented with pineapple peel flour (Aparecida Damasceno et al., ).…”
Section: Wastes and Byproducts From Tropical Fruits And Their Currentmentioning
confidence: 99%